2011
DOI: 10.12659/msm.881700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormone replacement therapy (HRT) on periodontal status of postmenopausal women

Abstract: SummaryBackgroundThe risks/benefits balance of hormone replacement therapy (HRT) is controversial. The aim of this study was to assess the periodontal status of a postmenopausal women group receiving HRT and to determine the effects of HRT on clinical measures of periodontal disease.Material/MethodsNinety-one postmenopausal women, 52 taking HRT (HRT+) and 39 not taking HRT (HRT−), completed the study. Clinical parameters measured included visible supragingival plaque, probing pocket depth (PD) and clinical att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 59 publications
(84 reference statements)
2
41
1
5
Order By: Relevance
“…The participants’ ages ranged from 32 to 72 years. Only three studies reported the race/ethnicity of the participants (Norderyd et al, ; Pizzo et al, ; Wang, LaMonte et al, ), being composed of Caucasian women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants’ ages ranged from 32 to 72 years. Only three studies reported the race/ethnicity of the participants (Norderyd et al, ; Pizzo et al, ; Wang, LaMonte et al, ), being composed of Caucasian women.…”
Section: Resultsmentioning
confidence: 99%
“…The PPD was registered in six sites per tooth of the participants in four studies (Çekici et al, ; Norderyd et al, ; Persson et al, ; Pizzo et al, ). Tarkkila et al () reported PPD on 4 sites per tooth of postmenopausal women while López‐Marcos et al () recorded the deeper value of PPD in each dental surface analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier also, the authors reported similar findings in their study. 5 Pizzo et al 15 evaluated the periodontal parameters in female subjects with postmenopausal status receiving hormone replacement therapy (HRT).…”
Section: Discussionmentioning
confidence: 99%
“…It is selectively expressed in osteoclasts and plays pivotal role in degradation of bone matrix [56]. It is the only known mammalian proteinase that can solubilize both, type I and type II collagens increased in gingival crevicular fluid in patients with periodontitis, which correlated with an increased concentration of RANKL.…”
Section: Cathepsin K Inhibitorsmentioning
confidence: 99%